1951
DOI: 10.1139/z51-027
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS ON THE GRASSHOPPER, MELANOPLUS MEXICANUS MEXICANUS (SAUSS.) (ORTHOPTERA: ACRIDIDAE), OF VARYING THE NITROGEN CONTENT IN ITS FOOD PLANT

Abstract: iMelanoplzrs mexicanzrs mexicanus (Sauss.), from time of hatching, was fed on wheat (Renown) grown in nutrient solutions of varying nitrogen content. Some wheat was produced with an average nitrogen content of 6.16% (dry weight), some with 4.29Yq, and some with 3.33%. Survival and development were greatest on the high nitrogen wheat, least on the low. On the low nitrogen wheat no individuals developed beyond the last nymphal instar. Neither weight of adults nor the sex ratio was affected by the various foods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1955
1955
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…Joern and S. Mole, unpublished data). Egg production in several grasshopper species can be quite responsive to changes in dietary N as well (Smith and Northcott 1951;McCaery 1975). Likewise, switching females from high-to low-protein diets resulted in an immediate decrease in egg production and resorption of terminal oocytes (McCaery 1975); opposite results were obtained after switching females from low-to highprotein diets.…”
Section: Importance Of Dietary Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Joern and S. Mole, unpublished data). Egg production in several grasshopper species can be quite responsive to changes in dietary N as well (Smith and Northcott 1951;McCaery 1975). Likewise, switching females from high-to low-protein diets resulted in an immediate decrease in egg production and resorption of terminal oocytes (McCaery 1975); opposite results were obtained after switching females from low-to highprotein diets.…”
Section: Importance Of Dietary Nmentioning
confidence: 99%
“…More needs can be satis®ed if nutritional resources are abundant compared with limiting situations. As a consequence, growth or reproduction will drop o or cease if the diet becomes inadequate (McCaery 1975;Bernays 1982), and survival (re¯ecting maintenance capabilities) varies with diet quality as well (Smith and Northcott 1951;Joern and Gaines 1990). While selecting food resources, grasshoppers simultaneously obtain protein and energy in addition to other nutrients, including water (Dadd 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Nethcott, 1951) studied the effects of various food plants on the rearing of Melanoplus mexicanus and reported that consumption and utilisation rate differs with different food plants. Barbosa and Jane (1979) reported that the development and survival of gypsy moth (Lymantria dispar) larvae is strongly influenced by the host plant upon which they feed.…”
Section: Reproductive Potential Of a Mylitta On Different Forestry Hmentioning
confidence: 99%
“…

The direct approach to the study of the food requirements of insects is to rear them on artificial diets. Studies on insect growth and egg-laying rates on plant food raised in this way have been reported by Smith & Northcott (1951) (Melanoplus mexicanus mexicanus (Sauss.) have been raised successfully in this way (Bottger, 1942;Beck & Lilly, 1949).

…”
mentioning
confidence: 99%